Analisis Efektivitas Penerapan Sistem Insentif Bagi Karyawan Pt X - Maria Yuliana Postel; MartaUli Septiana Manalu; Hwihanus Hwihanus (Akuntansi, 2024)
This article discusses the analysis of the effectiveness of the implementation of the incentive system for employees. The purpose of this study is to determine the extent to which the incentive system can motivate employees to improve company performance. The method used in this research is interviews with employees of PT X. The results of this study indicate that the incentive system in this company has not been effective. This can be seen from the less than optimal achievement of several factors that affect the effectiveness of the implementation of the incentive system. Providing ineffective incentives can also make employees less enthusiastic in carrying out their work